Evaluation of mean platelet volume (MPV) levels in patients with synovitis associated with knee osteoarthritis. (March 2014) - Balbaloglu, Ozlem; Korkmaz, Murat; Yolcu, Sadiye; Karaaslan, Fatih; Beceren, N. Gökben Çetin
<x xml:space="preserve">Abstract</x> Platelet count, C-reactive protein (CRP) and neutrophile countings are markers those reflect the inflammatory response. Mean platelet volume (MPV) is a simple indicator of platelet size and has been known to be a marker of platelet activity. Some platelet markers, including MPV, have been investigated to have relation with inflammation. MPV is inversely correlated with inflammation in inflammatory bowel diseases, rheumatoid arthritis, and ankylosing spondylitis, as shown in the previous studies. In this study, we aimed to investigate the levels of MPV in patients with synovitis of knee osteoarthritis. 147 patients diagnosed with synovitis associated to osteoarthritis, 191 patients with knee osteoarthritis, and 121 patients between the same age range who did not have joint complaints (control group), totally 459 participants were included to our study. MPV results of these groups were compared. We found a significant difference between the patient group with synovitis associated with osteoarthritis of knee and patients with knee osteoarthritis in MPV blood level (p < 0.0001), similarly a significant difference was found between the patient group with synovitis associated with osteoarthritis of knee and the control group (p < 0.0001). There was no significant difference between the knee osteoarthritis patient group and the control group (p = 0.78). We found a significant relation between MPV and ESR in the patient group with synovitis of osteoarthritis (p = 0.004). According to the Pearson correlation, it is found that there is a negative relationship between CRP and MPV variables in those of knee osteoarthritis patients. This correlation coefficient is statistically significant at the 10% level (p = 0.058). We could not find a relation between CRP and MPV in patients with the osteoarthritis group, but we found negative correlation (p = 0.65). Significant relationship was not found between ESR and MPV variables at the 10% level; the p value is 0.34. In the control group no correlation was found between CRP–MPV (p = 0.69) and ESR–MPV (p = 0.798). MPV levels may be beneficial in osteoarthritis with synovitis patients. MPV levels may be considered as a marker of inflammation but further comprehensive prospective trials are needed in osteoarthritis associated with synovitis patients.